Recent faulting along Gorontalo fault based on seismicity data analysis and lineament mapping - Efendi Hasan Arif (EDP Sciences, 2021)
We focused our study to characterize the geometry and activity of Gorontalo fault. We analysed reviewed the ISC seismic catalogue and the BMKG relocated earthquake events available for the time period of 1960 to 2021, located along the expected location of this fault. In addition, we analysed continuous record from local seismic observatory available for the same period. Further, we mapped the lineaments using 8.3-m resolution DEMNAS data. Tens on shallow earthquakes occurred in the vicinity of this fault with a range magnitude of M 2 to 3. Our lineament analysis however does not reveal distinctive pattern that may indicate the fault manifestation at the surface. The NW-SE trending lineaments are coincidence with the mapped trace of Gorontalo Fault. The weak surface manifestation of the fault scarp may be related to the tropical climatic condition of the area which may obliterate the faulting topography. However, we observed alignment of the seismicity distribution with the mapped NW-SE lineament, indicating that the lineament is likely representing active fault and these earthquakes are associated with faulting along this fault. Our study provide indication that the Gorontalo Fault is active and further study is necessary to investigate subsurface geometry and mitigate its seismic hazards.